Soil CO2 emission and short-term soil pore class distribution after tillage operations - Silva, Bruna de Oliveira [UNESP]; Moitinho, Mara Regina; Santos, Gustavo André de Araújo [UNESP]; Teixeira, Daniel De Bortoli; Fernandes, Carolina [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2019)
Alongside the agricultural development in Brazil, concerns have arisen about its environmental impacts, such as the emissions of CO2 resulting from soil cultivation and management practices in agricultural production systems. The aim of this study was to investigate the temporal variation in CO2 emissions and soil physical attributes in response to the process of soil particle rearrangement after soil tillage operations. The study was conducted in three adjacent areas of 10 × 3 m, subjected to two soil tillage systems: (i) rotary hoe + conventional leveling harrow, representing an intensive soil tillage (IT); (ii) disc harrow + leveling harrow, characterizing a reduced tillage (RT). The soil of the third area was not tilled, representing the no-tillage (NT) system. Daily measurements of soil CO2 emission (FCO2), soil temperature, soil moisture, pore class distribution, bulk density, penetration resistance, water-free pore space, weighted mean diameter, aggregate stability index, total organic carbon, and particulate organic carbon were performed during a period of 29 days after soil tillage. On the first day after tillage, FCO2 was 87% higher in the plot under IT (3.86 μmol m−2 s−1) than RT (2.06 μmol m−2 s−1) and 147% higher than in the plot under NT (1.56 μmol m−2 s−1). The variations in soil density and penetration resistance declined as of the 12th day after tillage. This effect was considered a natural process of soil consolidation and influenced the temporal variation of soil CO2 emissions. Pore class distribution is an essential physical attribute to explain the temporal variations of soil CO2 emissions, and these classes are influenced by the applied management. Therefore, the study of these attributes must be taken into account when assessing the variation of CO2 emissions from agricultural soils.
Keywords: No-tillage; Soil porosity; Soil respiration; Soil tillage